2022
DOI: 10.3390/molecules27072293
|View full text |Cite
|
Sign up to set email alerts
|

Rutin Promotes Pancreatic Cancer Cell Apoptosis by Upregulating miRNA-877-3p Expression

Abstract: (1) Background: pancreatic cancer is one of the most serious cancers due to its rapid and inevitable fatality, which has been proved very difficult to treat, compared with many other common cancers. Thus, developing an effective therapeutic strategy, especially searching for potential drugs, is the focus of current research. The exact mechanism of rutin in pancreatic cancer remains unknown. (2) Method: three pancreatic cancer cell lines were used to study the anti-pancreatic cancer effect of rutin. The potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that Rutin can reduce vancomycin-induced renal tubular apoptosis by inhibiting apoptosis, reducing intracellular reactive oxygen species, and improving mitochondrial dysfunction ( Qu et al, 2019 ). Rutin upregulates miR-877-3p expression, inhibits Bcl-2 transcription and induces apoptosis in pancreatic cancer cells ( Huo et al, 2022 ). Rutin also inhibits autophagy and Akt activation-mediated apoptosis and attenuates adriamycin-induced cardiotoxicity ( Ma et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Rutin can reduce vancomycin-induced renal tubular apoptosis by inhibiting apoptosis, reducing intracellular reactive oxygen species, and improving mitochondrial dysfunction ( Qu et al, 2019 ). Rutin upregulates miR-877-3p expression, inhibits Bcl-2 transcription and induces apoptosis in pancreatic cancer cells ( Huo et al, 2022 ). Rutin also inhibits autophagy and Akt activation-mediated apoptosis and attenuates adriamycin-induced cardiotoxicity ( Ma et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rutin used in this study was obtained by ethanol extraction from tartary buckwheat powder, the purity of rutin prepared by us reached more than 96% and stored in our laboratory as previously described 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Supress proliferation, increase apoptosis via upregulating miR-877-3p in Panc-1, SW-1990, and MiaPaCa-2 cells Huo et al 119 Exerts antioxidant action and increases apoptosis in combination with orlistat Saleh et al 120 Abbreviations: EGF, epidermal growth factor; GSK, glycogen synthase kinase; mTOR, mammalian target of rapamycin; NF-κB, nuclear factor kappa B; PARP, poly ADP ribose polymerase; ROS, reactive oxygen species; STAT3, signal transducer and activator of transcription 3; TGF, transforming growth factor; VEGF, vascular endothelial growth factor.…”
Section: Rutinmentioning
confidence: 99%
“…237 In a recent study, three different pancreatic carcinoma cell lines (Panc-1, SW1990, and MiaPaCa-2) treated with rutin (isolated from tartary buckwheat) showed suppressed proliferation and increased apoptosis via upregulating the miRNA-877-3p. 119 Furthermore, the anticancer property of rutin in combination with orlistat was tested against Panc-1 cells and the other two breast cancer models (EAC and MCF-7). Their results showed that the combinatorial treatment of both drugs exerted antioxidant action and apoptosis in tumor cells, signifying rutin's potential for future anticancer therapies.…”
Section: Anticancerous Propertiesmentioning
confidence: 99%
See 1 more Smart Citation